Subsídios para um currículo integrado a partir do olhar dos professores participantes do Projeto Voluntários da Paz - Casadei, Silmara Rascalha (2010)
The following study aims at identifying subsidies for an integrated curriculum, from the point of view of those teachers who participated on the Peace Volunteers Project, which was developed in an independent school in the city of Santo André, São Paulo recognised by the UNESCO Programme of Associated Schools. Using as a metaphor the image of a kaleidoscope, it shows ten years of the project. It also presents the theories in the light of the scholars from the University of La Cornunã, Jurjo Torres Santomé who has developed in depth research on the theme, the main guidance of UNESCO for the education in the XXI Century, besides some reflections of Abramowics, Apple and Beane, Bernstein, Freire, Sacristan, Bruner, Machado, among other scholars of relevant importance. Teachers opinions and ideas were analysed bearing in mind a qualitative approach and all the data collected were supported by the researched theories. To promote the discussion between practice and theory in the light of an integrated curriculum, the study shows that some aspects such as the importance of the life history of the teacher, the interdisciplinary meetings, the local and global context and the intention of the education for the peace among men and the environment are necessary points of view that can subsidize an integrated curriculum